The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1471-0528.16084
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and perinatal health: a systematic review

Abstract: Background Physical, psychological and sexual intimate partner violence (IPV) has been described in the literature as different types of IPV experienced by women during pregnancy all over the world. Objectives To review and summarise systematically the empirical evidence on the links between IPV during pregnancy and the perinatal health of mothers and fetuses/neonates. Search strategy MEDLINE (Ovid), CINAHL, Embase, Nursing@ovid (Ovid) and LILACS were searched (2008–2018). Selection criteria Observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 68 publications
3
41
0
2
Order By: Relevance
“…52 The studies in the literature provide pieces of evidence of the relationship between both low birth weight and preterm labor and violence during pregnancy. [2][3][4][5][6]54 The result that women exposed to IPVP experienced obstetric problems, which was determined by this study, was compatible with the literature.…”
supporting
confidence: 91%
“…52 The studies in the literature provide pieces of evidence of the relationship between both low birth weight and preterm labor and violence during pregnancy. [2][3][4][5][6]54 The result that women exposed to IPVP experienced obstetric problems, which was determined by this study, was compatible with the literature.…”
supporting
confidence: 91%
“…The prevalence of violence during pregnancy in Guyana was high at 9.2%, which is likely to have significant downstream health consequences for these women and their children (1, 2) including on measures that we were not able to directly assess in the current study, including risk of miscarriage, premature birth, low birthweight, perinatal death, and reduced healthcare utilization by pregnant women; these outcomes should be included in future research (7)(8)(9). Similar to other studies, controlling partner behavior was significantly associated with maternal experience of physical violence during pregnancy (14,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Attention to IPV during pregnancy (IPV-P) has increased due to the substantial health consequences for women and children and high prevalence (5,6). IPV-P may cause injury to the mother and the fetus due to direct trauma; adverse maternal health behaviors such as delayed and/or reduced antenatal care, reduced skilled delivery care, and increased smoking during pregnancy (5,7); negative reproductive health outcomes including miscarriage, premature rupture of membranes; preterm delivery, unsafe abortion, low birthweight, and perinatal death (5,8,9); increased risk of child abuse and neglect in the postnatal period (10); and other physical and mental health outcomes including physical impairment and depression (5,11) as well as suicide ideation (12) and suicide attempt (13). A systematic review of the mental health sequelae of IPV-P in low-and middle-income countries found that it increased the odds of antenatal depression by 1.69-3.76 and the odds of postnatal depression by 1.46-7.04, with suicide ideation rates during pregnancy ranging from 5% to 11% and during postpartum 2% to 22% (14).…”
mentioning
confidence: 99%
“…Besides, VAW and IPV might increase in pregnancy/postpartum or has deleterious effects on motherinfant bonding and child outcomes (21). In a recent systematic review, Pastor-Moreno et al (22) showed a relation between psychological IPV and adverse outcomes, including premature rupture of membranes, preterm birth, urinary tract infections, and late entry into prenatal care. In addition, sexual IPV was associated with late entry into prenatal care, urinary tract infections, and low birth weight.…”
Section: Psychiatric Consequences Of Violence Against Women During Covid-19 Pandemicmentioning
confidence: 99%